Zinner's syndrome: clinical case of a rare pathology - D. A. Dobroserdov; M. P. Kuchinskii; N. A. Filatova; L. T. Nalgieva (Вестник урологии, 2023)
Zinner’s syndrome is a rare congenital urogenital anomaly characterised by the triad of seminal vesicle cyst, ipsilateral renal aplasia, and seminal duct obstruction. According to the published data, the incidence of seminal vesicle cysts with ipsilateral renal agenesis is 0.0046%, but the true incidence appears to be higher. The article presents a rare clinical case of patient K, 17 years old, followed since birth with a solitary right kidney. The patient was repeatedly examined (ultrasound, cystography, urography, abdominal MRI, pelvic CT). The boy was admitted to our clinic with the diagnosis of "Solitary right kidney" and pelvic cystic formation detected according to the last CT scan. MRI examination of the small pelvis, cystoscopy, diagnostic laparoscopy, puncture of the cystic mass were performed. The diagnosis of "Zinner's syndrome" was made. The size of the cyst did not change during follow-up.